How Can Sharia-Compliant Investments Minimize Risk Without Sacrificing Returns? - Prameswari, Amelia; Martia, Dina Yeni; Rois, Muhammad (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
This research examines how sharia-compliant investments can minimize risk without sacrificing returns through portfolio optimization. Using the Single Index Model (SIM) and Capital Asset Pricing Model (CAPM), this study evaluates the performance of stocks in the IDX Sharia Growth index from November 2022 to October 2024. Data from 30 companies were analyzed, with stock returns based on daily closing prices, Bank Indonesia Certificates as a proxy for risk-free returns, and the Composite Stock Price Index for market returns. Stocks were ranked based on Excess Return to Beta (ERBi), and the optimal portfolio was determined using the cut-off rate. The results show that the SIM portfolio (12 stocks) offers higher returns with lower risk, while the CAPM portfolio (15 stocks) provides similar returns to individual stocks but with lower risk. The findings confirm that sharia-based portfolio optimization effectively reduces risk while maintaining returns, providing valuable insights for investors seeking sharia-compliant financial strategies.